2020
DOI: 10.1038/s41598-020-59893-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGF-β signalling in combination with nal-IRI plus 5-Fluorouracil/Leucovorin suppresses invasion and prolongs survival in pancreatic tumour mouse models

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive malignancies. TGF-β is strongly expressed in both the epithelial and stromal compartments of PDAC, and dysregulation of TGF-β signalling is a frequent molecular disturbance in PDAC progression and metastasis. In this study, we investigated whether blockade of TGF-β signalling synergizes with nal-IRI/5-FU/LV, a chemotherapy regimen for malignant pancreatic cancer, in an orthotopic pancreatic tumour mouse model. Compared to nal-IRI/5-FU/LV tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…However, the mechanism by which NP treatment inhibits CCDC80 expression requires further study. Recent study suggested that activation of TGF-β signaling could inhibit the expression of CCDC80 (Hong et al, 2020), which suggested that NP might influence the expression of CCDC80 by activating other signaling pathways. Additionally, our data revealed that NP treatment activated ERK1/2, even when co-treated with CCDC80 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which NP treatment inhibits CCDC80 expression requires further study. Recent study suggested that activation of TGF-β signaling could inhibit the expression of CCDC80 (Hong et al, 2020), which suggested that NP might influence the expression of CCDC80 by activating other signaling pathways. Additionally, our data revealed that NP treatment activated ERK1/2, even when co-treated with CCDC80 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, TGF-β signaling accelerates tumor progression in advanced-stage pancreatic cancer by inducing EMT, metastasis, invasion, migration, and immune evasion ( 27 ). In fact, the contribution of TGFβ to metastases has been well proven in pancreatic cancer ( 28 , 29 ). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, EMT has been reported to contribute to pancreatic cancer cells' drug resistance (14) as well as relate strongly to poor prognosis of PDAC (15). Moreover, recent evidence has been lent to genetic, molecular, and biochemical mechanisms mediating the EMT process in progression and metastasis of pancreatic cancer (16,17), which strengthens the view of EMT as a cancer hallmark. While prior reviews have largely focused on molecular (e.g., Elaskalani et al (18), Safa (19)) or biochemical mechanisms (e.g., inflammation, Khalafalla and Khan (20), Wang et al (21)) underlying the EMT process in pancreatic cancer, this essay depicts recent evidence for the role of EMT-regulating mechanisms in pancreatic cancer in terms of genetic, molecular, and biochemical aspects.…”
Section: Introductionmentioning
confidence: 86%
“…An extension of this research stream should be to investigate the role of other tumor suppressing genes such as PTEN and CDKN2A (46) as genetic regulating factors underlying EMT process in proliferation of pancreatic cancer. In addition, the suppressing role of CCDC80 in EMT processes should be examined in other carcinoma types than pancreatic (16), hepatocellular (47), and lung carcinoma (48).…”
Section: Implications For Future Researchmentioning
confidence: 99%